School Nurse Poverty Education: Why It Is Important to Your Practice. (November 2021) - Fliesher, Susan; Neumann, Linda; Curtis, Mary P.
School nurses are seeing increased numbers of children who are living in poverty. The Missouri Community Action Program Poverty Simulation was presented to school nurses to increase their awareness of what it might be like to live in poverty and the related healthcare barriers. Participants shared their reactions and knowledge gained in the simulation in a postparticipation survey with the simulation facilitators. Some participants shared practice changes that they made as a result of their participation in the simulation, which included use of additional referral resources, being less judgmental, and increased empathy.